Production of Low Calorie Bakery Product with Pleasant Flavour, Antioxidant and Antimicrobial Activities - Hussein Ahmed M.S.; Shaheen Mohamed S.; Abdel-Kalek Hanan H.; El-Nor S.A.H. Abo (Polish Journal of Food and Nutrition Sciences)
Aromatic plants are considered sources of antioxidants, antimicrobial and favouring agents. Four aromatic plants (Thymus vulgaris L., Foeniculum vulgare, Pimpinella anisum L. and Trigonellafoenum-graecum L.) were analysed in the study. Yoghurt was used to produce a low calorie pie. Chemical and rheological parameters, baking performance, staling rate and sensory properties of the pie were investigated. Volatile aroma compounds were anal-ysed with GC and GC/ MS, and antioxidant activity was evaluated by DPPH and β-carotene assays. The incorporation of yoghurt and some aromatic plants in the pie improved protein, fat, fibre, ash, and minerals contents and allowed achieving about 19% reduction in calories. Sensory evaluation of pie containing the mixture of aromatic plants showed its superior sensory quality. In addition, it could be concluded that aromatic plants were able to inhibit the growth of yeast, mould and bacteria and to prolong the storage periods of pie compared with the control.